STUDI FENOMENOLOGI: COPING STRESS GURU PENDAMPING KHUSUS DI SEKOLAH KRISTEN KALAM KUDUS PONTIANAK - Kristiani Sitio, Desi; Muhammad Diponegoro, Ahmad (Lafadz Jaya Publisher, 2024)
Teachers accompanying children with special needs have student-centered learning processes, are very responsible and have high work pressure. The pressure and burden of responsibility for special companion teachers in the profession has the potential to trigger stress. The aim of the study was to find out coping stress on special accompanying teachers at the Kalam Kudus Christian School, Pontianak. This study uses qualitative methods with a phenomenological approach. The method used in this research is qualitative research with a phenomenological approach. data collection will be done by interview and observation, and data analysis using content analysis. The results showed that research subjects used more emotion focused coping than problem focused coping to reduce stress levels.